Profile Of Antihypertensive Drug Use In Patients With Coronary Artery Disease At Prof. Dr. I.G.N.G. Ngoerah General Hospital (RSUP) In 2023 - Jeanan Aulia Arifin; Ida Ayu Alit Widhiartini; I Made Jawi (Green Publisher Indonesia, 2025)
Background: Coronary heart disease (CHD) is often triggered by atherosclerosis, with hypertension as a major risk factor. Managing hypertension through lifestyle modification and pharmacological therapy, such as ACE inhibitors, ARBs, beta-blockers, CCBs, and diuretics, is important to prevent further complications. Objective: To determine the profile of antihypertensive drug use in CHD patients at RSUP Prof. Dr. I.G.N.G. Ngoerah Denpasar in 2023. Methods: This was a descriptive study using a cross-sectional design. Data were collected retrospectively from medical records of CHD patients in 2023 after obtaining approval from relevant authorities. Data analysis was performed using IBM SPSS version 26. Results: The majority of patients were male (88%) and aged 56-65 years. Most resided in Denpasar with normal blood pressure and had comorbidities such as hypertension, type 2 diabetes mellitus, and chronic kidney disease. Beta-blockers were the most commonly used antihypertensive agents (32.3%), followed by diuretics (24.4%) and ACE inhibitors (19.6%). Triple-drug combination therapy was the most frequently used regimen, particularly the ACEi + BB combination, commonly administered once daily (OD). Conclusion: Most CHD patients were older males with multiple comorbidities. Beta-blockers were the most frequently prescribed antihypertensive drugs, followed by diuretics and ACE inhibitors. The prevalent use of combination therapy and once-daily regimens indicates an individualized treatment approach based on clinical conditions.